Isolation and Characterization of Bacterial Species from Enteric Fever Suspected Human Cases of Mymensingh Medical College Hospital - Al-Amin, M; Khan, MSR; Begum, F; Hasan, J; Asaduzzaman, M (Progressive Agriculture, 2013)
A total of 17 stool samples were collected from enteric fever suspected patients of Mymensingh Medical College Hospital, Mymensingh, Bangladesh. Results of morphological, biochemical examinations and pathogenicity test revealed Escherichia coli (47%), Klebsiella spp. (41%), Citrobacter spp. (29%). In cultural examination, all Escherichia coli showed metallic sheen on EMB agar, Klebsiella spp. showed moist shiny mucoid colonies and Citrobacter spp. showed large convex colorless dwarf colonies on MacConkey agar. In biochemical examination, all the isolates fermented five basic sugars with the production of acid and gas where the Citrobacter spp. were late lactose fermenter. Escherichia coli was indole and MR positive but V-P negative, Klebsiella spp. were V-P positive but MR and Indole negative and Citrobacter spp. were MR positive but V-P and Indole negative. All isolated bacterial species were sensitive to ciprofloxacin but resistant to amoxicillin. Salmonella typhi or Salmonella paratyphi organisms were not present in the stool samples examined. This may be due to collection of samples from patient having antibiotic therapy with Ceftriaxone through intravenous route for 3 days prior to collection of samples. From this study, it may be concluded that Escherichia coli, Kelbsiella spp. and Citrobacter spp. may be commonly present in enteric fever suspected patients or they may produce enteric fever like symptoms in human. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16857 Progress. Agric. 20(1 & 2): 85 92, 2009